ANALISIS STRUKTUR INTERNAL BAHASA PADA LAGU ‘ÂMMIYYAH MIȘRIYYAH “BAHEBBIK YÂ BELÂDY” - Azimah, Nahdliyyatul; Kusumawati, Endah (Lisanul Arab: Journal of Arabic Learning and Teaching, 2021)
The study aims to analyze the Egyptian colloquial song “Bahebbik Yā Belādy” in the perspectives of hermeneutics and the internal structures of the language that consist of phonology, morphology, syntax, and semantics. It is a qualitative- descriptive study. The researchers collected data by conducting observation, interview and literature review. The results of the research show that: (1) there are phonemic elements found in the song, which are: changing pronunciation of some letters, prolonging a vowel, tilting, and transmitting specific phonemes, (2) there are morphological elements found in the song that include the forms of past tense, present tense, isim fa'il, and isim maf'ul. Moreover, (3) there are grammatical elements found in the song, which are: the arrangement of the nominative and verbal sentences, and two prefixes of the present tense verb, the uses of the subject, and (م.....ش) for the prohibition, (4) in the perspective of semantics, there are only lexical and metaphor meanings found in the song. Keywords: Internal Structures of the Language, Egyptian colloquial Song, Bahebbik Yā Belādy. تجريد البحث تهدف الدراسة إلى تحليل الغناء العامي تحت موضوع "بحبك يا بلادي" من حيث هيرمينوتيكية و الهياكل الداخلية اللغوية التي تتكون من علم الأصوات و القواعد النحوية والصرفية و الدلالية. تعتبر هذه الدراسة نوعية- وصفية . تسلك الباحثة جمع البيانات من خلال الملاحظة و المقابلة والوثائق. و تدل على النتائج التالية : (1) توجد عناصر علم الاصوات منها: تغيير نطق بعض الحروف وإطالة الحروف المتحركة والإمالة ونقل الصوت المحدد، (2) و توجد العناصر الصرفية التي تشتمل على صيغ الفعل الماضي والفعل المضارع واسم الفاعل واسم المفعول. علاوة على ذلك (3) توجد العناصر النحوية منها: ترتيب الجملة الإسمية والفعلية وبادئتان للفعل المضارع ، واستخدام اسم الفاعل أكثر وكذلك (م....ش) للنهي، (4) و من ناحية الدلالة يوجد المعنى الأصلي والقياسي.